Analysis of Accounting Information Systems in the Payroll Cycle to Increase the Effectiveness of Internal Control at CV. Percetakan Independent Palembang in 2019 - Meyvira Permata; Harsi Romli; Leriza Desitama Anggraini (International Journal of Community Service & Engagement, 2023)
This study aims to analyze the payroll accounting information system to improve internal control at CV Percetakan Independent Palembang. The theory used was the American Statement of Basic Accounting Theory (ASOBAT) and the Theory of Technology Acceptance Model (TAM). Data were collected through interviews, observation, and documentation. This study implemented a descriptive approach to analyze data. The results show that there were several weaknesses in the company's payroll accounting information system that could weaken the company's internal control, namely: 1) several financial functions that double as a part responsible for financial reporting and company administration; 2) a number of financialfunctions that concurrently acted as a company in charge of recording every transaction; 3) employee attendance record file still was still manual.